How to conquer air pollution : a Japanese experience - Nishimura, H. (Hajime), 1933-; ScienceDirect eBooks (Amsterdam ; New York : Elsevier ; New York, N.Y., U.S.A. : Distributors for the U.S. and Canada, Elsevier Science Pub. Co., 1989)
Many parts of the world suffer from urban air pollution and, despite the vast amount of knowledge about its causes, most countries are slow to implement counter-measures. An outstanding exception is Tokyo which, once blanketed in a mantle of smog, now enjoys ``clean'' air in spite of highly concentrated activity and congested traffic. Based on the successful Japanese experience, this book describes all aspects of the measures necessary to combat air pollution. It begins with a well-documented history of the fight against air pollution and describes the processes and mechanisms of reaching a social consensus on pollution control. The essential steps in the process are the establishment of ambient air quality standards, the introduction of the total allowable mass of emission, and the legal control of each emission based on diffusion equations. The scientific background to this approach is fully explained, from epidemiology to computer simulations of air quality. An up-to-date account of emission control technology is also given, and the controversial issue of health damage compensation is examined, based on actual experience. An important feature of the book is that it is written by authors who were actually in the forefront of the battle against air pollution in Japan. Two of them worked successively as Director General of the Bureau of Air Quality of the central government, and a third helped local governments to force the central government to implement the most stringent auto-emission controls in the world. The book is intended not only for scientists, engineers and administrative planners dealing with pollution control, but also for anyone concerned about the serious global problem of urban air pollution.
1. History of Air Pollution Control in Japan. 2. Health Effects of Air Pollution. 3. Emission Control Technology. 4. Monitoring and Simulation. 5. System for Regulation. 6. The Pollution-Related Health Damage Compensation Law. Subject Index.
Includes bibliographical references.
Print version record.
Elsevier
Keywords: Air -- Pollution -- Japan; Air quality management -- Japan; Air -- Pollution -- Law and legislation -- Japan; Air -- Pollution -- Japon; Air -- Qualité -- Gestion -- Japon; TECHNOLOGY & ENGINEERING -- Environmental -- Pollution Control; Air -- Pollution; Air -- Pollution -- Law and legislation; Air quality management; Japan; Electronic books